Improving Palliative Care Knowledge of nurses caring for heart failure patients - Sana Ali; Kim McMillan; Freya Kelly (BMC Palliative Care)
Abstract Background Approximately 80% of patients with advanced heart failure (HF) die within five years of diagnosis and may benefit from palliative care (PC). PC is underutilized in HF patients. One barrier is nurses’ insufficient knowledge of PC. This quality improvement project aimed to enhance the PC knowledge of nurses caring for patients with HF in a Canadian tertiary care setting. Method This project was guided by the Knowledge-to-Action framework. Semi-structured interviews were conducted to identify nurses’ learning needs, which informed the development of the educational sessions. These sessions were delivered using hybrid, virtual, and asynchronous modalities. PC knowledge tests were used pre- and post-intervention to evaluate the nurses’ PC knowledge. The data were presented using descriptive statistics. Results Thirteen nurses attended the educational sessions. Ten responses were received for both the pre- and post-knowledge tests. Most participants had more than 10 years of experience, were 41 years or older, and had received prior PC training. The post-test showed improved knowledge (90–100%) of opioid use for symptomatic relief of dyspnea, advanced care planning (ACP) discussions, and communication processes. Knowledge of NSAID use in patients with HF increased by 60%. All nurses demonstrated an understanding of ACP concepts before and after the education. PC concept understanding increased from 80 to 90%. Conclusions Educational sessions improved nurses’ PC knowledge, and future education should emphasize improving PC perceptions and symptom management. However, evaluating the effectiveness of PC education is challenging because of low participation. Further research with a larger sample, longer implementation time, ongoing evaluation of PC knowledge, and nurses with diverse ages and experiences is required to understand the impact of PC education.